Immune Modulation Using Mistletoe (Viscum album L.) Extracts Iscador - Büssing, Arndt (Arzneimittelforschung, 2006)
One repeatedly finds that mistletoe (Viscum album L.) extracts show immune-modulating effects. This is also true in many cases in the experimental setting. Many of the experimental trials cannot, however, be transferred to the clinical situation - or only in a limited way. The aim of this work was to pursue the question of the extent to which the function of immune-competent cells can be influenced by mistletoe extracts. To do this, 3 clinical studies were carried out. Results from the first two studies will be presented here.In a prospective observational study with defined inclusion and exclusion criteria, the impact of two different doses of Iscador® M (Malus) or Iscador® Qu (Quercus) on the function and number of T-lymphocytes from tumor patients was studied. The immunological tests took place monthly during the first six months. Thirty-one patients were included in the slow dose group and 36 patients in the group with swift dose escalation. It was postulated that too swift increase in dosage would lead to stronger local reactions and impairment of the stimulation capacity of T-cells taken ex vivo and incubated for 72 h. The evaluation showed that patients with stronger local reactions at the injection site have an impairment of mitogen-induced stimulation capacity of T-cells. However, patients with stronger local reaction showed a significant decrease of HLA-DR+ T cells as compared to patients with moderate or without any local reactions.In a GCP-conform, controlled bicentric phase II study the aim was to investigate the efficacy of a perioperative intravenous mistletoe extract application on the modulation of operation-induced immune suppression. For this purpose 105 patients with breast cancer were recruited. At the treatment centre the patients received an infusion of 1 mg Iscador M Spezial prior to the start of an operation, in addition to normal medication, while this was not practised at the control centre. The primary trial objective was the oxidative burst in granulocytes taken from patients ex vivo prior to surgery, and 1 and 3 days after. In order to take account of possible differences in the two groups, propensity scores were used as the basis for a matched pair analysis. It became clear that inhibition of the granulocyte function in the treatment group was significantly less marked (p < 0.001; Wilcoxon). Mistletoe extract-related adverse reactions were not observed. Thus this special form of application could minimise the immune suppression triggered by anaesthesia and operation stress.
Keywords: Granulocytes; Iscador®; Lymphocytes; Mistletoe extract, application route, immunomodulation; Viscum album L.